Sex determination using gonial angle during growth spurt period: a direct examination - Hariemmy, Monica; Boedi, Rizky Merdietio; Utomo, Haryono; Margaretha, Mieke Sylvia (Indonesian Journal of Dental Medicine, 2018)
Background: In forensic medicine and medicolegal, sex determination is an important step of an identification process. Parts of human skeleton that can be used for identification are cranium, pelvis, and mandible. There are several anthropometry tools in sex determination methods i.e shape of mandible, mental, gonial angle. Gonial angle in adults is an excellent tool for sex determination. However, bone density and masticatory force may change the value of gonial angle. Purpose: The objective of this study was to examine sex determination method using gonial angle in children during grow spurt period and external factors. Methods: There were 104 randomly selected subjects (51 boys and 53 girls) aged 7-12 years old. The subjects were grouped into prolonged sun exposure-hard diet (group A) and low sun exposure-soft diet (group B). The measurements were made using goniometer. Results: The mean of gonial angle of female children was greater than the male children. There was no significant difference between group A and B. Conclusion: Gonial angle can be used for sex determination in grow spurt period, and external factors did not affect sexual dimorphism.